Participatory Design in Developing Gamification on Introducing Renewable Energy to Teenage Students - Burhan, Rifaatul Mahmudah; Rante, Hestiasari; Arini, Nu Rhahida; Hasnaoui, Abir (The Indonesian Journal of Computer Science, 2022)
The Covid-19 pandemic has had an impact on all sectors, including the world of education. Learning that has been done using traditional methods such as books has turned to virtual media such as zoom, google meet, and social media. This makes students less interested and feel bored. In addition, the current use of energy sources continues to increase which results in the depletion of energy sources. this is due to a lack of knowledge and awareness regarding renewable energy and energy sources. In this study, we used a participatory design method that involved teachers and students in collecting data that was relevant to everyday life. We also conducted interviews and asked students and teachers about their study habits and the meaning of renewable energy and their daily life related to energy, the impressions they have of attending classes, and any opinions for further improvement.This method is proven to help provide outstanding results in decision-making to build gamification applications as learning media that can attract interest and motivation to learn for students, especially junior high school students. As a result of the analysis of students' understanding and concern about renewable energy, it was analyzed as "enough" with a percentage of 57.1%. Based on the results of research and student opinions, we would like to suggest that there must be the development of learning methods or alternative media such as gamification for junior high school students.